2008
DOI: 10.1074/jbc.m708429200
|View full text |Cite
|
Sign up to set email alerts
|

K+-Cl- Cotransporter-3a Up-regulates Na+,K+-ATPase in Lipid Rafts of Gastric Luminal Parietal Cells

Abstract: Gastric parietal cells migrate from the luminal to the basal region of the gland, and they gradually lose acid secretory activity. So far, distribution and function of K ؉ -Cl ؊ cotransporters (KCCs) in gastric parietal cells have not been reported. We found that KCC3a but not KCC3b mRNA was highly expressed, and KCC3a protein was predominantly expressed in the basolateral membrane of rat gastric parietal cells located in the luminal region of the glands. KCC3a and the Na ؉ ,K ؉ -ATPase ␣1-subunit (␣1NaK) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…The expression of these transporters has been documented in several epithelial cells either at the apical or basolateral membranes (17). Recent work has suggested an important role for KCC3 and KCC4 in acid secretion in the stomach (13)(14)(15). KCC3 knockout mice develop arterial hypertension (44), and KCC4 knockout mice exhibit renal tubular acidosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of these transporters has been documented in several epithelial cells either at the apical or basolateral membranes (17). Recent work has suggested an important role for KCC3 and KCC4 in acid secretion in the stomach (13)(14)(15). KCC3 knockout mice develop arterial hypertension (44), and KCC4 knockout mice exhibit renal tubular acidosis (6).…”
Section: Discussionmentioning
confidence: 99%
“…KCC3a and KCC4 are mainly expressed in epithelial-type cells (13,14). Recently we found that KCC3a is expressed in the basolateral membrane of gastric parietal cells located at the luminal region of gastric glands and coimmunoprecipitated with Na ϩ ,K ϩ -ATPase (15). Exogenous expression of KCC3a in LLC-PK1 cells up-regulates Na…”
mentioning
confidence: 99%
“…The exogenous expression of KCC3a recruited a1NaK into lipid rafts, accompanying an increase of the ATP-hydrolyzing activity and the phosphorylation level of Na ϩ , K ϩ -ATPase. 18) In contrast, exogenously expressed KCC3b did not co-immunoprecipitate with a1NaK, accompanying no change in the Na (Fig. 2), and the NH 2 -terminus of KCC3a may be a key region for association with Na (Fig.…”
Section: Cellular Physiology Of Channels and Transporters In Gastroinmentioning
confidence: 99%
“…Recently we found that KCC3a and KCC4 were expressed in the basolateral and apical canalicular membranes of gastric parietal cells, respectively 18,19) (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation